KEYNOTE LECTURE - Materiality, Movement & Meaning: Architecture and the Embodied Mind - Hale, Jonathan (Proceedings of the Annual Architectural Research Symposium in Finland, 2014)
Writing in 1993 on the relations between technology, language and cognition, the anthropologist Tim Ingold provided what appeared to be a perfectly clear and precise definition of the tool as a ‘prosthetic’ extension of the body: “A tool, in the most general sense, is an object that extends the capacity of an agent to operate within a given environment.” (Ingold, 1993: 433) In the context of Ingold’s discussion of the agency of tools and technologies, it could be argued that this statement actually assumes what it sets out to explain - that is, it assumes that we already know what constitutes an ‘agent’, and that we can therefore speak of the tool as a simple linear extension of an agent’s ability. In fact, it may be more accurate to say – if we consider this question within the ‘long duration’ of the evolutionary emergence of the modern human being - that the tool, in reality, came first. Or, at the very least, I want to argue that technology is in fact mutually co-implicated in the gradual emergence of human agency over this long evolutionary timescale, and – the reason why I think it’s so important – it continues to be so today in terms of our everyday experience. The claim I want to make by the end of the paper is that the kind of buildings that bear witness to this process of emergence are the ones that best support our sense of well-being, in the broadest possible terms. To begin with, I’m thinking here of two related examples of emergence: firstly the ontogenetic process – how we as human beings mature into apparently rational sense-making individuals, when we didn’t start out that way at birth – and secondly, what we might call (after the editor of Alexander Luria’s book on Language and Cognition) the ‘micro-genetic’ process by which we make sense of our ongoing flow of embodied experience ‘in real-time’ as it were, of what actually goes on in that curious overlapping of immediate past with anticipated future that we usually refer to as ‘the present moment’. Of course I’m thinking here of Edmund Husserl’s analysis of the consciousness of time as a multi-layered experience of what he called ‘retentions’ and ‘protentions’, and also of the more recent work by the neurophilosopher Daniel Dennett in his book Consciousness Explained, from 1991, where he explores these ideas in a much more accessible way, also drawing on more recent experimental data from research in the neurosciences. In order to explore this apparently circular relationship between the human and the technological, in what follows I will describe some examples of the ways in which we engage with technologies on a day to day level, and how the process of ‘incorporation’ – literally, absorbing into our body-image, or more accurately our body-schema – entails a number of important cognitive consequences. In the final part of the paper I will also try to outline what I think this might mean for the continuing relevance of tectonic articulation and materiality in architecture, for example, in the creation of engaging and richly layered environments that contain visible traces of both the processes of construction and occupation –spaces that invite engagement with both the bodies and minds of future building users. And this is the reason why I think this way of thinking about time, as just mentioned, as a multi-layered continuum of past recollections and future projections – especially in relation to tools and technologies - is so important for architects to consider.